Evaluation in Latin America and the Caribbean: An Overview of Recent Developments - Thomaz Chianca; Brandon W. Youker (The Evaluation Center at Western Michigan University, 2004)
This article discusses the state of evaluation in Latin America and the Caribbean and outlines the professional organizations and publications in the region.